I teatri degli anni Duemila: Rinnovamento estetico e nuove esigenze economico-organizzative in Babilonia Teatri, Fibre Parallele, Menoventi, TeatrInGestAzione - Screpis, Valeria (Mimesis Journal, 2024)
Since 2000 the Italian theater, especially in experimental theater’s area, has gone through a phase of transformation determined by exogenous factors (economical, historical, cultural) and endogenous factors (new aesthetics; institutional and legislative changes). The aesthetic renewal and the ever more dynamic global context have produced new challenges. The artists of the 2000s have to faces these challenges developing new management models that combine aesthetic vision and economical needs. This research, through the comparative observation of four theater companies (Babilonia Teatri, Fibre Parallele, Menoventi, TeatrInGestAzione), intends to investigate the modalities according to which each of them develop and manage the relationship between artistic and economic dimension.